Pianistin tulkinnan muodostuminen Robert Schumannin Sonaatista op. 11 - Kärkkäinen, Matilda (Taideyliopiston Sibelius-Akatemia, 2016)
The formation of a pianist's interpretation of Robert Schumann's Sonata op. 11 is the topic of this thesis. I approached the piece from different points of view during my practicing process and while writing this paper. The first point of view was acquainting myself with the historical and biographical facts of the piece as they are in literature regarding Schumann. The second aspect that came to the fore was the analysis of the piece in terms of harmony and musical form. In this I relied on my own analysis and that of Charles Rosen. Playing the piece on a modern grand piano and on a piano of Schumann's time and comparing these two experiences stood out as a third point of view. Schumann's Sonata op. 11 is connected with many kinds of symbolism, in regard to his personal life as well as in regard to his professional aspirations. The piece offers many challenges also in relation to harmonic and formal analysis. Especially the formal analysis leads to questions that hardly ever have unequivocal answers or solutions. In this thesis I compare the influence of differing analytical findings to the actual playing of the piece. At the beginning of my practicing process with Schumann's Sonata op. 11 on an modern instrument I was perplexed by some problems regarding sonority and sound, and my confusion led me to try the piece on a fortepiano. The comparison of both the sound image and the physical playing is a part of my thesis. The final conclusions of my work are as follows: After analysing the harmonies and musical form of Sonata op. 11 my interpretation of it turned out different from my initial and intuitive way of playing it. Secondly, there are notable differences, especially in the choice of tempi and the use of pedals, between the two kinds of instruments. Thirdly, the experiences with a fortepiano changed my perception of the ideal sound image when playing the piece also when I played it on a modern grand piano.

Tutkielmassani perehdyin Robert Schumannin Sonaatin op. 11 tulkinnanmuodostumiseen. Lähestyin teosta harjoitusprosessini ja tutkielmani kirjoittamisen aikana erilaisista näkökulmista, joista ensimmäinen oli teoksen taustojen kartoitus lähdekirjallisuuteen nojaten. Toisena aspektina esiin nousi teoksen harmonia- ja muotoanalyysi omaan analyysiini ja Charles Rosenin analyysiin perustuen ja kolmantena soittokokemuksen vertailu fortepianon ja modernin flyygelin välillä. Schumannin Sonaattiin op. 11 liittyy monenlaista symboliikkaa niin säveltäjän yksityiselämästä kuin hänen ammatillisista pyrkimyksistäänkin. Teos on myös harmonia- ja muotoanalyysin kannalta haasteellinen, sillä varsinkin sen muotoa analysoitaessa on vaikea löytää yksiselitteisiä ratkaisuja. Tutkielmassani vertailen erilaisten analyysin tuomien vaihtoehtojen vaikutusta soittotapahtumaan. Schumannin Sonaatin op. 11 parissa tekemäni harjoitusprosessin alussa törmäsin soinnillisiin ongelmiin soittaessani sitä modernilla flyygelillä, mikä johti minut tutkimaan teoksen soittamista fortepianolla. Vertailen tutkielmassani sointikuvan ja soittotapahtuman eroavaisuuksia erilaisten soittimien parissa. Loppupäätelminä tutkimuksessani ovat seuraavat seikat: Harmonia- ja muotonanalyysi toi eriasteisia muutoksia intuitiiviseen tapaani soittaa Schumannin Sonaattia op. 11. Toiseksi sen soittamisessa fortepianolla ja modernilla flyygelillä on merkittäviä eroavaisuuksia varsinkin tempovalinnoissa ja pedaalinkäytössä. Teoksen soittaminen fortepianolla johti erilaisen sointikuvaihanteen tavoitteluun myös soittaessani sitä modernilla flyygelillä.
Keywords: Schumann, Robert.; musiikkianalyysi; sonaatit; piano; sonaattimuoto; fortepiano; DocMus